The Power of Giving A Strategy for Building Morale at the Border - Dongsombat, Suphachok (Chophayom Journal, 2026)
This academic article aims to examine the role of Buddhist monks in strengthening the morale of military personnel within the context of contemporary security society. It focuses on explaining the role of belief capital as a mechanism that integrates religion, society and security, an area that remain underexplored in security studies, which have traditionally emphasized strategic, political and military dimensions. The study employs documentary analysis, field observation and the synthesis of interdisciplinary literature in Buddhism, sociology, and security studies. The findings are interpreted through the conceptual frameworks of dāna (generosity), belief capital, social capital and psychological resilience. The findings indicate that belief capital functions as a form of spiritual resource that enhances the psychological stability of military personnel through the transmission of Buddhist teachings, religious rituals and the presentation of sacred amulets by Buddhist monks. These practices extend beyond conventional religious ceremonies, serving as cultural skilful means (upāya) that alleviate fear, strengthen psychological resilience and enhance soldiers’ preparedness for high-risk missions. Furthermore, military personnel are not merely recipients of belief capital but also active agents in reproducing and transmitting it through the sharing of sacred objects, mutual encouragement and the cultivation of solidarity within military units. Consequently, belief capital evolves into social capital that reinforces trust, cohesion and organizational resilience within the security sector. This article proposes a new body of knowledge by conceptualizing belief capital as both a form of cultural and a spiritual resource that contributes to human security. It demonstrates that belief capital serves as an integrative mechanism linking Buddhism, psychology, sociology and security studies, thereby broadening the conventional understanding of security from a predominantly physical perspective to one that encompasses psychological and social dimensions. The findings also provide practical implications for the development of policies aimed at enhancing the morale and psychological well-being of military personnel within the Thei socio-cultural context.